IMPLEMENTATION OF COMMUNITY EMPOWERMENT FROM THE PERSPECTIVE OF THE QUR'AN IN BOJONG JENGKOL VILLAGE, CIAMPEA DISTRICT, BOGOR REGENCY, WEST JAVA PROVINCE - Supriadi, Cecep; Kohar, Ade (Khidmatul Ummah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Poverty is still an unresolved problem. The low level of education is the cause of the lack of knowledge and skills possessed by the community, so that the community is helpless. This community service aims to provide knowledge and strengthen the role of the community in empowering each other in Bojong Jengkol Village, Ciampea District, Bogor Regency, West Java Province. The method used in this research is a participatory and collaborative approach from local communities. Data was obtained through interviews, observation and documentation studies. The results of this research show that community empowerment needs to be carried out as indicated in the Qur'an so that people can change their behavior and get a better life. It is hoped that the results of this research can help the government and society in improving the quality of life both in terms of education, economics and social strata.